2017
DOI: 10.1101/144139
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolutionary dynamics of incubation periods

Abstract: The incubation period of a disease is the time between an initiating pathologic event and the onset of symptoms 1 . For typhoid fever 2, 3 , polio 4 , measles 5 , leukemia 6 and many other diseases 7-10 , the incubation period is highly variable. Some affected people take much longer than average to show symptoms, leading to a distribution of incubation periods that is right skewed and often approximately lognormal [8][9][10] . Although this statistical pattern was discovered more than sixty years ago 8 , it r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…3a,e, 4 and 5), in agreement with previous reports 34,35 . The log-normal nature of the ℓ b and AR, which we confirm theoretically (equation (10a)), is observed frequently in natural systems and stems from the underlying independent random variables [34][35][36][37] . This confirms that the distribution of AR is ultimately determined by that of ℓ b , provided the variability in growth rate remains low, as reported previously 38 .…”
supporting
confidence: 76%
“…3a,e, 4 and 5), in agreement with previous reports 34,35 . The log-normal nature of the ℓ b and AR, which we confirm theoretically (equation (10a)), is observed frequently in natural systems and stems from the underlying independent random variables [34][35][36][37] . This confirms that the distribution of AR is ultimately determined by that of ℓ b , provided the variability in growth rate remains low, as reported previously 38 .…”
supporting
confidence: 76%
“…Epidemics occur when the latent period is close to 20 and 42 h. We note that large epidemics are likely across a larger range of latent period modes in the second cluster due to the larger variance in the distribution of latent periods. This is a consequence of the fact that incubation (and thus latent) periods follow a log-Normal distribution for which higher mean results in a higher variance [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, they appeared continuously during a period of up to 3 weeks, even though a single pathogen strain was used to infect a single host variety. This observation is consistent with recent modelling of distributions of incubation periods (Ottino‐Loffler et al ., ), but it contradicts the established view in the literature on Z. tritici , according to which lesions appear after a symptomless period of approximately 2 weeks (Kema et al ., ; Steinberg, ). Shaw () used pycnidiospores from the natural field population of Z. tritici to inoculate wheat plants in the greenhouse and found that lesions appeared continuously during a period of up to 25–30 days; however, the asynchronicity in lesion appearance could have resulted from the variation in latent period between different pathogen strains as well as the ‘developmental’ asynchronicity within a single pathogen genotype that was observed in the present study.…”
Section: Discussionmentioning
confidence: 99%